Mastering Dreamweaver 4 and Fireworks 4 - Crowder, David A. (Sybex Inc., 2001)
Includes hand coding and the layout view found in Dreamweaver, along with the pop-up menu creator found in Fireworks. Includes practical advice on developing your site's architecture, and enhancing interactivity into your site's design.